Executive Processes and Emotional and Behavioural Problems in Youths Under Protective Measures - Moreno-Manso, Juan Manuel; García-Baamonde, M.ª Elena; Guerrero-Barona, Eloísa; Godoy-Merino, M.ª José; Guerrero-Molina, Mónica; Barbosa-Torres, Carlos (Frontiers in Psychology, 2021)
This research studies the executive processes of youths under protective measures between 13 and 18 years of age, as well as the emotional problems they have and the presence of behavioral problems, such as difficulties to control and direct attention, to control one’s own behaviour and inhibit inadequate or ineffective responses (hyperactivity-impulsiveness) and problems related to emotional regulation. In addition, we study the presence of significant differences according to the sex of the youths. We also analyse to what extent the difficulties in the executive processes are related to and can predict the emotional and behavioral problems. The instruments used were Stroop’s Colour and Word Test (Stroop), the Paths Test (TESen) and the System of Evaluation for Children and Adolescents (SENA). The results indicated that the youths had difficulties in such executive processes as execution, speed and accuracy in carrying out tasks. Furthermore, they had emotion problems, among which the symptoms of anxiety are worthy of note; while attention deficit, hyperactivity-impulsiveness, and problems related to emotional regulation could also be observed. The data indicated greater difficulties in the executive processes for males than for females. There was a greater emotional symptomatology in the females, while there were greater deficits in attention and hyperactivity/impulsiveness in the males. Similarly, the deficits in the executive processes were related to and predicted emotional and behavioral problems. This research suggests the design of a structured programme focused on systematic training in real, daily situations, recommending the use of restorative techniques to work on the affected cognitive skills and techniques aimed at improving the youths’ emotion regulation.